Mujer y transmedialidad: creadoras de imágenes - García López, Miriam (Arte, Individuo y Sociedad, 2021)
M. Gloria Ríos Guardiola; Encarna Esteban Bernabé; M. Belén Hernández González (eds.). Academia del Hispanismo (Vigo), Serie Biblioteca Daphne, 2020, 206 pp. ISBN: 978-84-17696-30-6